PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS III 008 RAMBAH - Surya surya (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to improve the results of IPS learning in third grade students of SD Negeri 008 Rambah. The results of the study as follows. In the first cycle, at the first meeting of teacher activity reached 62.50% medium category, increased in the second meeting 4.17% to reach 66.67% medium category. While in cycle II, the first meeting of teacher activity reached 83.33% good category, and increased from the second meeting of cycle I as much as 16.66%. The second meeting reached 91.67% very good category, increased again from the previous meeting as much as 8.34%, from the description bove can be seen that the increase in teacher activity in learning by using Group Investigation type cooperative model.